Pelimpah ITB Golden Ratio: Inovasi Geometri Mercu Pelimpah untuk Kemudahan Perencanaan dan Kinerja Hidraulis yang Baik - Dantje Kardana Natakusumah; Syaeful Annas; Joko Nugroho; Eka Oktariyanto Nugroho; Arno Adi Kuntoro; Fitra Adinata (Jurnal Teknik Sipil, 2025)
Abstract A spillway is a critical hydraulic structure used to release excess water when the water surface elevation in a dam exceeds the normal limit. The discharge capacity is strongly influenced by its geometric profile. In Indonesia, ogee and circular spillways are the most commonly used types. The ogee spillway is known for its superior hydraulic performance but features a complex geometry that requires high construction precision. In contrast, the circular spillway offers a simpler design, yet lacks a standardized reference for crest curvature ratios. To address this issue, the Golden ratio Tipe Spillway was developed by applying the constant mathematical ratio φ ≈ 1.618 to the crest profile. The aim is to create a design that is simpler, visually harmonious, and still hydraulically efficient. Evaluation was conducted through numerical simulations using Flow 3D software, validated by physical model testing in the laboratory. Results show that while the ogee spillway remains the most optimal in terms of performance, the ITB Golden Ratio Spilway types A and B demonstrate comparable discharge capacity, safe pressure.   distribution, and low cavitation risk. These advantages make it a practical and reliable design alternative Keywords: Spillway crest, Flow-3D, physical model test, spillway design, ITB Golden ratio spilway.